2019
DOI: 10.1002/hbm.24623
|View full text |Cite
|
Sign up to set email alerts
|

Fronto‐parietal and temporal brain dysfunction in depression: A fMRI investigation of auditory mismatch processing

Abstract: Mismatch responses reflect neural mechanisms of early cognitive processing in the auditory domain. Disturbances of these mechanisms on multiple levels of neural processing may contribute to clinical symptoms in major depression (MD). A functional magnetic resonance imaging (fMRI) study was conducted to identify neurobiological foundations of altered mismatch processing in MD. Twenty‐five patients with major depression and 25 matched healthy individuals completed an auditory mismatch paradigm optimized for fMRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 51 publications
(111 reference statements)
2
20
0
Order By: Relevance
“…In patients, it has been shown that auditory cortex activation and auditory perception and processing are impaired in depression (Zwanzger et al, 2012; Bonetti et al, 2017; Zweerings et al, 2019). Moreover, age-related hearing loss has been associated with late life depression (Husain et al, 2014; Rutherford et al, 2018; Scinicariello et al, 2019), and in animals, chronic restraint stress decreased glucose metabolism in the auditory cortex (Wei et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients, it has been shown that auditory cortex activation and auditory perception and processing are impaired in depression (Zwanzger et al, 2012; Bonetti et al, 2017; Zweerings et al, 2019). Moreover, age-related hearing loss has been associated with late life depression (Husain et al, 2014; Rutherford et al, 2018; Scinicariello et al, 2019), and in animals, chronic restraint stress decreased glucose metabolism in the auditory cortex (Wei et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the widespread increase in GluN2A subunits following fluoxetine, we examined structural and synaptic adaptations in cortical areas that are not directly involved in the modulation of mood, such as sensory (including auditory) and motor cortices, which are impaired in depression and might be affected by fluoxetine treatment (Zwanzger et al, 2012; Frodl, 2017; Yin et al, 2018). We specifically evaluated the dendritic architecture and the synaptic properties of pyramidal neurons in the auditory cortex after fluoxetine treatment, an area that is disturbed in depression (Zweerings et al, 2019). Our results indicate that fluoxetine induces structural and functional adaptations compatible with increased network maturation.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, participants with UD had greater myelin in 6 visual regions and had reduced myelin in 3 regions (left V4t, left FFC, and left 7AL). While depression is not typically considered a disorder of dysfunctional sensory processing, somatic symptoms in depression have been well described 65 , and there are reports of both visual 66 and auditory 67 processing deficits in depression. Our results contribute to a growing body of literature documenting associations of depression with altered structure 12 and functional connectivity 68,69 in sensory regions.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the nature of attention deficits in depression and anxiety, especially in relation to sensory processing, is still lacking. Most research in anxiety and depression has focused on early pre-attentive and automatic visual and auditory processing and showed impaired deficits in early auditory and visual processing in depressed and anxious samples (Chang et al 2011;Kahkonen et al 2007;Qiu et al 2011;Schirmer and Escoffier 2010;Takei et al 2009;Weinstein 1995;Yang et al 2019;Zweerings et al 2019). However, sensory processing as modulated by attention has not been studied in depression and anxiety, which we plan to address in the current study by exploring attention performance on auditory and visual stimuli of individuals with elevated symptoms of depression and anxiety in comparison with individuals with low symptoms.…”
Section: Introductionmentioning
confidence: 99%